Larangan Ultra Vires (Exces De Pouvoir) dalam Tindakan Pemerintahan (Studi Komparasi Konsep antara Sistem Hukum Anglo Saxon dan Sistem Hukum Kontinental) - Sri Nurhari Susanto (Administrative Law and Governance Journal, 2020)
This research aims to determine the use of authority by government agencies is legality. Specifically, to find out more about the prohibition of Ultra Vires (Exces De Pouvoir) in Government Actions (Comparative Study of Concepts between the Anglo Saxon Law System and the Continental Legal System). The results of the study indicate that First, the form of government agency action prohibition in the form of excès de pouvoir (ultra vires), both in the Anglo Saxon legal system (Britain, USA, Australia, etc.) and Continental especially France includes also the prohibition of abuse of authority (abuse of power, detournement de pouvoir). Second, the Prohibition of abuse of authority (detournement de pouvoir) in France has been developed into 3 (three) variants, namely the Administrative Agency has the purpose / aims to achieve goals that are entirely other than the public interest, and as a personal goal. Keywords: Prohibition of Ultra Vires, Government Actions, Legal System. Abstrak Penelitian inimbertujuan untuk mengetahui Larangan Ultra Vires (Exces De Pouvoir)  dalam Tindakan Pemerintahan (Studi Komparasi Konsep  Antara Sistem Hukum Anglo Saxon Dan Sistem Hukum Kontinental). Hasil penelitian menjukan bahwa Pertama, Bentuk larangan tindakan badan pemerintah yang berupa excès de pouvoir  (ultra vires), baik dalam sistem hukum Anglo Saxon (Inggris, USA, Australia, dll)  maupun Kontinental khususnya Prancis meliputi juga larangan penyalahgunaan wewenang (abuse of power, detournement de pouvoir). Kedua, Larangan penyalahgunaan wewenang (detournement de pouvoir) di Prancis telah dikembangkan ke dalam 3 (tiga) varian, yaitu Badan Administrasi memiliki tujuan/bertujuan untuk mencapai tujuan yang sepenuhnya selain bagi kepentingan umum, dan sebagai tujuan pribadi. Kata Kunci: Larangan Ultra Vires, Tindakan Pemerintahan, Sistem Hukum.